The Impact of VAAs on (non-Voting) Aspects of Political Participation: Insights from Panel Data Collected During the 2017 German Federal Elections Campaign - Manavopoulos, Vasilis; Triga, Vasiliki; Marschall, Stefan; Wurthmann, Lucas Constantin (My University, 2019)
Thus far, research on the effects of Voting Advice Applications has focused on some aspects of voting behavior, whether, for example, these online tools impact citizens’ likelihood to vote or their voting choices. Relatively under-researched remain questions concerning the relationship between using VAAs and other forms of engagement with politics, such as involvement in electoral campaigns and information seeking about politics and parties. This paper seeks to examine effects in these behaviors associated with VAA-use employing panel data generated during and after the period of the German Bundestag Federal Election in September, 2017. The data from roughly 1120 participants, sampled to be representative of the German internet users, were collected in four waves, 1 month before the election at the earliest and several weeks following at the latest. We find that VAA-use is positively associated with consuming information about politics through other media (e.g. TV) and other election-related information-seeking activities, such as reading party programmes. On the other hand, we find no statistically significant relationship between VAA-use and interpersonal talk about politics or more active engagement with electoral campaigns such as attending party rallies.
Keywords: Voting Advice Applications